Research on the New Camellia Variety "Four Seasons Treasure" and Its Applications - Liu, Li; Liu, Xinkai (International Journal of Agriculture and Food Sciences Research, 2025)
This research paper details the development and characteristics of a new camellia cultivar, 'Four Seasons Treasure'. Bred through artificial hybridization using the robust red camellia 'Jinpan Lizhi' as the female parent and the unique Camellia azalea Wei as the male parent, this new variety exhibits desirable and stable traits. 'Four Seasons Treasure' is an evergreen shrub with a semi-open form, obovate leaves, and medium-sized, double-petaled pink flowers. A key characteristic is its extended flowering period, beginning in July and lasting for approximately six months, which helps bridge the summer-autumn blooming gap common in traditional camellias. The paper describes the cultivar's morphological characteristics, outlines optimal cultivation techniques for both potted and ground planting, and discusses its application potential in urban greening and Chinese flower arrangement. The development of 'Four Seasons Treasure' represents a significant step in Sichuan camellia breeding, contributing to efforts aimed at creating more adaptable, long-blooming varieties for wider use in urban landscapes.